2020
DOI: 10.1002/jctb.6345
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate (PHA) purification through dilute aqueous ammonia digestion at elevated temperatures

Abstract: BACKGROUND Purification of polyhydroxyalkanoates (PHA) is a challenging step, given the difficulty of achieving high PHA purity, while maintaining polymer integrity, in a sustainable and cost‐efficient manner. This study evaluated the potential of dilute ammonia digestion as a method to purify PHA from mixed microbial consortia. RESULTS Digestion temperatures were critical to the obtainable purity and the amount of recovered PHA. At temperatures below 75 °C (regardless of the incubation time and ammonia concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…However, NH 4 OH could be a better alternative than NaOH since it is claimed to be potentially easier to be recycled ( Mannina et al, 2019 ); additionally, NH 4 OH performances can be improved by applying specific pretreatments ( Jiang et al, 2015 ): if a NaClO pretreatment is applied, the polymer purity increases, whereas if a freeze-drying pretreatment is applied the polymer recovery increases ( Table 5 ). Recently Burniol-Figols et al (2020) investigated the effect of NH 4 OH on PHA purity, recovery, and molecular weight: long incubation times and high NH 4 OH concentrations negatively impact the polymer recovery but have no influence on its purity, whereas increasing the temperature of the digestion both purity and recovery increase. However, even if at 140°C the highest recovery and purity is achieved (90 and 83%, respectively), a drastic reduction of the molecular weight is also observed (from 0.6 MDa at 30°C to 0.08 MDa at 140°C), suggesting an optimal temperature range of 75–115°C to get high recovery of PHA (above 90%) and maintaining the molecular weight of PHA at reasonable values (0.2 MDa).…”
Section: Extraction Of Pha From Mixed Microbial Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NH 4 OH could be a better alternative than NaOH since it is claimed to be potentially easier to be recycled ( Mannina et al, 2019 ); additionally, NH 4 OH performances can be improved by applying specific pretreatments ( Jiang et al, 2015 ): if a NaClO pretreatment is applied, the polymer purity increases, whereas if a freeze-drying pretreatment is applied the polymer recovery increases ( Table 5 ). Recently Burniol-Figols et al (2020) investigated the effect of NH 4 OH on PHA purity, recovery, and molecular weight: long incubation times and high NH 4 OH concentrations negatively impact the polymer recovery but have no influence on its purity, whereas increasing the temperature of the digestion both purity and recovery increase. However, even if at 140°C the highest recovery and purity is achieved (90 and 83%, respectively), a drastic reduction of the molecular weight is also observed (from 0.6 MDa at 30°C to 0.08 MDa at 140°C), suggesting an optimal temperature range of 75–115°C to get high recovery of PHA (above 90%) and maintaining the molecular weight of PHA at reasonable values (0.2 MDa).…”
Section: Extraction Of Pha From Mixed Microbial Culturesmentioning
confidence: 99%
“…In fact, mechanical properties of polymers (e.g., the tensile strength) are affected by their molar mass; molecular weight values above 0.5 MDa and polydispersity index below 3 are usually considered acceptable thresholds for these thermoplastic polymers, being typical of quite homogeneous chain lengths that can be processed through injection molding techniques without any compromising reduction in the total polymer length ( Fiorese et al, 2009 ). Some studies have reported for example that a molecular weight below 0.1 MDa causes severe deterioration of the mechanical properties for P(HB-HV) ( Burniol-Figols et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, disruption of NPCM was obtained by using non-ionic surfactants as pretreatment before PHA extraction with DMC ( Colombo et al, 2020 ) and by treating the biomass with ammonia solutions at high temperatures ( Burniol-Figols et al, 2020 ). In a previous study ( Lorini et al, 2020 ), NaClO digestion was investigated for PHA recovery from MMC produced at pilot scale.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied methods for recovering PHAs have been summarized in recent reviews ( Kosseva and Rusbandi, 2018 ; Pérez-Rivero et al, 2019 ) and can be grouped into two main categories: solvent extraction and digestion of the NPCM (non-PHA cellular material). Up to now, regarding the MMC PHA-rich biomass, the use of several non-chlorinated solvents ( Werker et al, 2014 ; Samorì et al, 2015 ) and, more recently, the disruption of NPCM through chemical agents ( Burniol-Figols et al, 2020 ) and surfactants ( Colombo et al, 2020 ) have been investigated. In the view of MMC-PHA production at industrial scale and a subsequent market scenario, specific chemo-mechanical and thermal properties of the polymer need to be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…So far, different approaches have been suggested, but there is still room for improvement and innovation on this particular aspect. Burniol-Figols et al evaluated an innovative PHA purification through dilute aqueous ammonia digestion (purity 86 ± 0.8%), and they compared it with reference processes, such as dissolution in chloroform and precipitation in methanol (purity 99 ± 0.2%), or also acid-mediated digestion with H 2 SO 4 , followed by a treatment with NaOCl and subsequent washing with water and centrifugation (purity 98 ± 2.6%) [ 50 ]. Moreover, more environmentally friendly purification processes were proposed like the use of dimethyl carbonate for extraction, followed by a purification step with 1-butanol via reflux.…”
Section: Pha: Biosynthesis and Propertiesmentioning
confidence: 99%